KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MOTIVASI KERJA SDM DI LINGKUNGAN SMK NEGERI 4 SUKABUMI - Mutakin, Ade Anwar; Neng Yunita Nurmala Dewi, Neng Yunita Nurmala Dewi; Mochammad Ristianto, Mochammad Ristianto; Hanafiah, Hanafiah; Muchtarom, Muchtarom (PT. Solusi Komunikasi Terapan, 2024)
The principal has a big influence on increasing the work motivation of human resources in the SMKN 4 Sukabumi environment. The general aim of this research is to analyze the influence of school principal leadership on HR work motivation and the specific aim of this research is to determine and analyze leadership styles, policies, and the results of school principal leadership styles and policies on HR performance motivation. The theoretical basis for work motivation used is from Veithzal (2005: 455). This research uses a qualitative method with a case study approach. Based on the results of the data analysis and discussion, it can be concluded that the Principal’s leadership style can influence HR performance motivation. It turns out that it is the collaborative/together leadership style that teachers tend to accept when receiving instructions, because according to the survey, almost 100% of respondents answered that the collaborative leadership style is very teacher friendly. expect from a school principal. because the leadership style of a school principal that is in accordance with the teacher’s wishes has a great influence on HR performance motivation.